2020
DOI: 10.2196/preprints.19468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internet-Based Supportive Interventions for Family Caregivers of People With Dementia: Systematic Review and Meta-Analysis (Preprint)

Abstract: BACKGROUND Caring for people with dementia is perceived as one of the most stressful and difficult forms of caring. Family caregivers always experience high levels of psychological burden and physical strain, so effective and practical support is essential. Internet-based supportive interventions can provide convenient and efficient support and education to potentially reduce the physical and psychological burden associated with providing care. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Recent systematic reviews have demonstrated that WBIs can enhance health outcomes among patients with chronic diseases such as diabetes 25 and dementia. 26 Moreover, with the rapid growth of internet access rates worldwide and the popularisation of web-based devices, the practical feasibility of WBIs has increased. 17 25 26 In recent years, the increasing number of randomised controlled trials (RCTs) [27][28][29][30][31] related to WBIs on women's UI, in particular in the context of the COVID-19 pandemic, has demonstrated a growing need for supplementary strategies that can enhance existing services and provide better assistance to UI management for women.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Recent systematic reviews have demonstrated that WBIs can enhance health outcomes among patients with chronic diseases such as diabetes 25 and dementia. 26 Moreover, with the rapid growth of internet access rates worldwide and the popularisation of web-based devices, the practical feasibility of WBIs has increased. 17 25 26 In recent years, the increasing number of randomised controlled trials (RCTs) [27][28][29][30][31] related to WBIs on women's UI, in particular in the context of the COVID-19 pandemic, has demonstrated a growing need for supplementary strategies that can enhance existing services and provide better assistance to UI management for women.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%